Short-and Long-Term Expression of Vegf: A Temporal Regulation of a Key Factor in Diabetic Retinopathy - Bucolo, Claudio; Barbieri, Annalisa; Viganò, Ilaria; Marchesi, Nicoletta; Bandello, Francesco; Drago, Filippo; Govoni, Stefano; Zerbini, Gianpaolo; Pascale, Alessia (Frontiers in Pharmacology, 2021)
To investigate the role of vascular endothelial growth factor (VEGF) at different phases of diabetic retinopathy (DR), we assessed the retinal protein expression of VEGF-A164 (corresponding to the VEGF165 isoform present in humans, which is the predominant member implicated in vascular hyperpermeability and proliferation), HIF-1α and PKCβ/HuR pathway in Ins2Akita (diabetic) mice at different ages. We used C57BL6J mice (WT) at different ages as control. Retina status, in terms of tissue morphology and neovascularization, was monitored in vivo at different time points by optical coherence tomography (OCT) and fluorescein angiography (FA), respectively. The results showed that VEGF-A164 protein expression increased along time to become significantly elevated (p < 0.05) at 9 and 46 weeks of age compared to WT mice. The HIF-1α protein level was significantly (p < 0.05) increased at 9 weeks of age, while PKCβII and HuR protein levels were increased at 46 weeks of age compared to WT mice. The thickness of retinal nerve fiber layer as measured by OCT was decreased in Ins2Akita mice at 9 and 46 weeks of age, while no difference in the retinal vasculature were observed by FA. The present findings show that the retina of the diabetic Ins2Akita mice, as expected for mice, does not develop proliferative retinopathy even after 46 weeks. However, diabetic Ins2Akita mice recapitulate the same evolution of patients with DR in terms of both retinal neurodegeneration and pro-angiogenic shift, this latter indicated by the progressive protein expression of the pro-angiogenic isoform VEGF-A164, which can be sustained by the PKCβII/HuR pathway acting at post-transcriptional level. In agreement with this last concept, this rise in VEGF-A164 protein is not paralleled by an increment of the corresponding transcript. Nevertheless, the observed increase in HIF-1α at 9 weeks indicates that this transcription factor may favor, in the early phase of the disease, the transcription of other isoforms, possibly neuroprotective, in the attempt to counteract the neurodegenerative effects of VEGF-A164. The time-dependent VEGF-A164 expression in the retina of diabetic Ins2Akita mice suggests that pharmacological intervention in DR might be chosen, among other reasons, on the basis of the specific stages of the pathology in order to pursue the best clinical outcome.